Impact of information usefulness and adoption in social media on purchase intention :Evidence of Indonesia - Subekti, Toni Ahmad; Nugroho, Sahid Susilo (Universitas Muhammadiyah Surakarta, 2023)
The Product reviews on YouTube Channel offer information for consumers to evaluate products before making a decision. Understanding how consumers adopt the information and its impact on purchase intention becomes crucial. This study aims to determine the influence of information usefulness and information adoption on purchase intention on YouTube channels. The study developed a research model based on the Information Adoption Model (IAM) and Theory of Reasoned Action (TRA). A survey design was employed to test the proposed linkages among variables with a sample size of 447 respondents by the purposive sampling method. The study deploys the partial least squares path modeling (PLS-SEM) to analyze the data. The results confirmed that relevance, comprehensiveness, source expertise, attitude toward information, and information usefulness positively affect information adoption and purchase intention. Additionally, attitude toward information has a positive influence on behavioral intentions. However, timeliness, accuracy, and source expertise do not have any significant relationship with the information usefulness.